2011
DOI: 10.1186/1757-7241-19-55
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital resuscitation evaluated by in situ simulation: a prospective simulation study

Abstract: BackgroundInterruption in chest compressions during cardiopulmonary resuscitation can be characterized as no flow ratio (NFR) and the importance of minimizing these pauses in chest compression has been highlighted recently. Further, documentation of resuscitation performance has been reported to be insufficient and there is a lack of identification of important issues where future efforts might be beneficial. By implementing in situ simulation we created a model to evaluate resuscitation performance. The aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
3
15
0
4
Order By: Relevance
“…12,17,23,25 In the present study, the 24 hour survival rates of both groups were as high as those reported in the literature.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…12,17,23,25 In the present study, the 24 hour survival rates of both groups were as high as those reported in the literature.…”
Section: Discussionsupporting
confidence: 78%
“…22 In several studies, the mean CPR starting time varied between 80 sec (1.3 min) and 341 sec (5.7 min). [23][24][25] In this study, the time for the arrival of the CBT to the arrest and the start of the CPR before and after the introduction of code blue was similar to the values presented in the literature. Our hospital is a four-floor building.…”
Section: Discussionsupporting
confidence: 69%
“…[3,[15][16][17] In this study, the mortality rate in the CB procedures was found to be 62.61% and the survival rate was 38.07%.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, it has been reported by Roessler et al [2], Kobayashi et al [3], and Lubrano et al [5] that the time taken to initiate chest compressions can be shortened when the new guidelines were followed. Although the 2010 ERC guidelines and the 2010 AHA guidelines for BLS are different in terms of procedures for checking the victim for a response and the time taken to activate the emergency response system and initiate chest compressions, we showed that all subjects achieved a shorter chest compression initiation time after completing their re-education according to the new AHA guidelines [6][7][8][9][10][11][12][13][14]. At the time when 2005-BLS was developed, health care providers were considered not to have ventilation equipment for cardiopulmonary arrest, indicating that BLS may have actually been performed without rescue breathing.…”
Section: Discussionmentioning
confidence: 85%